Faktor-faktor yang Mempengaruhi Minat dalam Pembelian Makanan: Promosi Media Sosial dan Label Halal sebagai Variabel Independen - Alfajri, Dian Rizky; Pratama, Irfan Aji; Said, Syihabudin; Atiah, Isti Nuzulul (Airlangga Journal of Innovation Management, 2026)
Driven by the fierce rivalry within the digital-age culinary MSME sector, this research addresses the conflicting empirical evidence surrounding how digital marketing, halal certification, and e-WOM shape purchasing interest. The research gap lies in the divergent results of prior studies and the limited empirical models integrating social media promotion, halal labelling, and e-WOM within a unified analytical framework in a religiosity-based local market context. This study aims to examine the effects of social media promotion, halal labelling, and e-WOM on consumer purchasing intention in culinary SMEs. A quantitative approach with a cross-sectional survey design was employed. Data were collected through structured questionnaires and analyzed using multiple linear regression to test both partial and simultaneous effects. Statistical evaluations demonstrate that while online promotion and halal tags notably drive purchasing decisions, peer-to-peer digital reviews (e-WOM) fail to show a meaningful partial impact. Simultaneously, the three variables significantly affect purchasing intention. The novelty of this study lies in developing an integrative model that combines digital communication dimensions and religious value–based trust attributes within a single empirical framework at the SME level. Theoretically, the study enriches digital and halal marketing literature, while managerially, it highlights the importance of optimizing promotional content and ensuring halal certification. Future research is recommended to adopt longitudinal designs and incorporate mediating variables such as trust and perceived risk to further refine the analytical model.